2022
DOI: 10.1001/jamanetworkopen.2022.16726
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Risk of Overdose or Mental Health Crisis After Opioid Dose Tapering

Abstract: Key Points Question Is opioid dose tapering associated with reduced longer-term risks of overdose, withdrawal, or mental health crisis in patients prescribed long-term opioids? Findings In this cohort study of 19 377 patients, in a posttaper period (beginning at least 12 months and extending up to 24 months after taper initiation) vs the pretaper period, the adjusted incidence rate ratios were 1.57 for overdose-withdrawal and 1.52 for a mental health crisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Both starting and stopping opioids were associated with overdose or suicide risk in another study; risk associated with stopping opioids was increased when patients had received opioids for longer durations. Death rates for overdose or suicide in one study increased immediately after starting or stopping treatment with opioids, with the incidence decreasing over approximately 3–12 months ( 214 ) in one study and persisting over 2 years in another study ( 215 ). In observational studies evaluating outcomes related to heroin use after discontinuation of prescription opioids, one study found that heroin use was associated with discontinuation of long-term opioid use ( 216 ); another study found that among persons experiencing heroin overdose, prescription opioid use in the past 12 months was common but discontinuation of long-term opioid use was uncommon ( 217 ).…”
Section: Recommendationsmentioning
confidence: 98%
“…Both starting and stopping opioids were associated with overdose or suicide risk in another study; risk associated with stopping opioids was increased when patients had received opioids for longer durations. Death rates for overdose or suicide in one study increased immediately after starting or stopping treatment with opioids, with the incidence decreasing over approximately 3–12 months ( 214 ) in one study and persisting over 2 years in another study ( 215 ). In observational studies evaluating outcomes related to heroin use after discontinuation of prescription opioids, one study found that heroin use was associated with discontinuation of long-term opioid use ( 216 ); another study found that among persons experiencing heroin overdose, prescription opioid use in the past 12 months was common but discontinuation of long-term opioid use was uncommon ( 217 ).…”
Section: Recommendationsmentioning
confidence: 98%
“…Additionally, a recent retrospective cohort study of patients on long-term, high-dose opioid therapy for pain found that the 1-year period following dose tapering was associated with increased risk of overdose and mental health crisis [ 18 ]. Further, a follow-up study found that the increased risk of these adverse events extended up to 2 years after taper initiation [ 23 ]. However, the limited research to date investigating the link between deprescribing opioids for pain and opioid-related harms has some important shortcomings, with most existing studies focusing on subpopulations that may not be representative of the broader population of people prescribed opioids for pain [ 16 , 18 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, observational studies have identified potential harms of these practices, including increased risks of heroin use, 9 substance use disorders, 10 care termination, 11 overdose or suicide deaths, 12 , 13 and emergency department use and hospitalizations for overdose, withdrawal, and mental health crises. 10 , 14 , 15 Additionally, tapering attempts, particularly without shared decision-making, could prompt patients to seek care elsewhere by changing insurance plans or physicians, 11 , 16 potentially disrupting care continuity for comorbid health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied tapering using predefined opioid dosing patterns that occur after periods of stable dosing. 14 , 15 However, prior research also suggests that many patients in routine clinical care experience complex and variable dosing patterns over time. 17 For example, a physician may temporarily increase the dose to treat acute pain, or abruptly discontinue opioids if there is evidence of nonprescribed drug use.…”
Section: Introductionmentioning
confidence: 99%